Molecular dynamics simulations on devitrification: the PbF2 case - Silva, MAP; Monteil, A.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (American Institute of Physics (AIP), 2002)
In this work molecular dynamics simulations were performed to reproduce the kinetic and thermodynamic transformations occurring during melt crystallization, vitrification, and glass crystallization (devitrification) of PbF2. Two potential parameters were analyzed in order to access the possibility of modeling these properties. These interionic potentials are models developed to describe specific characteristic of PbF2, and thermodynamic properties were well reproduced by one of them, while the other proved well adapted to simulate the crystalline structure of this fluoride. By a modeled nonisothermal heat treatment of the glass, it was shown that the devitrification of a cubic structure in which the Pb-Pb distances are in good agreement with theory and experiment. (C) 2002 American Institute of Physics.